2022
DOI: 10.1186/s42506-021-00100-2
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological distress related to the emerging COVID-19 pandemic and coping strategies among general population in Egypt

Abstract: Background Psychological distress is considered a threat to the mental health of human beings. This research was conducted at the beginning of the emerging COVID-19 pandemic, when most people had limited knowledge about coronavirus, mode of transmission, associated manifestations, with uncertainty about treatment, vaccine, future life, and coping capacity. This study examined the nature of the psychological distress related to the emergence of the coronavirus disease 2019 (COVID-19) pandemic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 35 publications
(25 reference statements)
0
17
2
Order By: Relevance
“…However, it was women who were affected by the perceived stressors with greater intensity and frequency, no matter their age group. Studies in adults showed that women scored higher on a range of coping styles compared to men ( Fluharty and Fancourt, 2021 ) and a positive correlation between distress and the use of coping mechanisms ( Elkayal et al, 2022 ). The prevalence of depression and anxiety has been reported to be higher among females, yet the pandemic has accentuated this difference ( Santomauro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was women who were affected by the perceived stressors with greater intensity and frequency, no matter their age group. Studies in adults showed that women scored higher on a range of coping styles compared to men ( Fluharty and Fancourt, 2021 ) and a positive correlation between distress and the use of coping mechanisms ( Elkayal et al, 2022 ). The prevalence of depression and anxiety has been reported to be higher among females, yet the pandemic has accentuated this difference ( Santomauro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…People have chosen various strategies for coping with the difficulties of lockdown (e.g. Elkayal et al, 2022;Fluharty and Fancourt, 2021;Sampogna et al, 2021). For instance, a study conducted in Spain has found that focusing on certain tasks, such as "not listening to the news" or "drinking alcohol and watching TV" to avoid thinking about the situation, was the most popular mechanism (65%), while turning to social networks was a distant second (17%).…”
Section: Introductionmentioning
confidence: 99%
“…Being a nurse or technician, living in rural areas, working in governmental, university/central, not working in private health facility protect against low adaptation (Table 2, 3). Elkayal et al (33) in their study among general population in Egypt found the most adaptive people were the residents in the cities with a monthly income sufficient enough to meet their needs; better adaptation methods were also seen among both divorced and highly educated people. The differences may be due to alternative target populations.…”
Section: Figure (1)mentioning
confidence: 96%